Factors affecting the preferred use of modern contraceptives in District Dang Nepal - Suprich Sapkota; Munawar Hussain Soomro; Prayas Gautam; Prakash Pant (College of Community Physicians of Sri Lanka, 2018)
Background: Improving reproductive health is central to achieving sustainable development goals on improving maternal health, reducing child mortality and eradicating extreme poverty. This requires access of the women to safe and effective methods of fertility control.   Objective: To identify the factors that affect the preferred use of modern contraceptives   Methods: A cross-sectional study was conducted in Ghorahi, District Dang, Nepal in 2015 among 176 married women of reproductive age currently on a modern contractive method. Simple random sampling method was used for recruiting the sample. Data were collected on the characteristics of women, their most preferred modern contraceptive method, and the currently used contraceptive method including its mode of supply and decision making status, using a semi-structured interviewer-administered questionnaire.   Results: Among 176 women in the sample, 30.1% were of 25-30 years in age while 79% were literate. Around 57% had adequate knowledge on modern contraceptives. With regard to current modern contractive practices, women relied on hospitals (38.6%) and family planning clinics (28.4%) as the main sources for contraceptives. Their decision on the current method was based on their own choice (60.8%) or of others (39.2%) while contraceptives were either self-prescribed (78.4%) or prescribed by others (21.6%). Depo-Provera (58.5%) was the most preferred modern contraceptive method while Norplant (2.8%) was the least preferred. Majority of the women (84.7%) were using contraceptives according to their preference. Among others, the most preferred method could not be practised due to denial by husband (51.9%), side effects (18.5%) and contraindications (29.6%). Current practice of women using the most preferred modern contractive method was significantly associated with decisions made on their own on contraceptives (p=0.01) and with self-prescribing of contraceptives (p=0.01).   Conclusions: The current use of modern contraceptives in the majority of women was according to their preference. This status could be further improved by conducting programs related to effective counselling to enable couples on decision making before adopting any modern contraceptives.